KAMUFLASE “PASSOBIS”: MENGUNGKAP MODUS OPERANDI DAN UPAYA MITIGASI - Alfiansyah Anwar; Andi Marlina; Purnama Suci; Arfian Alinda Herman; Fakhriyah Nur (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
In the ever-growing digital era, online fraud is a serious threat, especially the "Passobis" phenomenon in Sidrap Regency, South Sulawesi. This research aims to uncover the modus operandi of this fraud, analyze its impact, and develop effective prevention strategies. By using library research methods (library research), data was collected from various sources, such as journals, books, research reports, and credible media. The research results show that "Passobis" uses various modes, including fake prize draws, illegal online loans, and fraud based on social media, which often targets victims inside and outside the Sidrap area. The main driving factors for this phenomenon include economic pressure, low levels of digital literacy, and weak legal supervision. This study also identified that most of the perpetrators came from the Gen Z age group, with increasingly sophisticated modus operandi thanks to technological developments. The uniqueness of this research lies in its interdisciplinary approach which integrates analysis of Islamic criminal law and Indonesian criminal law. This research offers recommendations in the form of increasing digital literacy, public education, and strengthening cross-institutional cooperation to prevent and deal with online fraud. The implications of this research emphasize the importance of building collective awareness in society to protect themselves from the threat of cyber crime, as well as the need for legal policies that are more adaptive to the dynamics of digital crime in the modern era.